REFORMING THE COMMON AGRICULTURAL POLICY (2023 – 2027) – GOALS AND NEW SYSTEM SOLUTIONS – - Nikolić, Marija; Božić, Dragica; Božić, Ivan (Economics of Agriculture, 2025)
The Common Agricultural Policy (CAP) is crucial for ensuring the future of agriculture and the rural development in the EU. The shortcomings of CAP in the previous period, challenges related to the global economic and geopolitical situation, the increasing need for environmental preservation and the necessity to mitigate climate change have led to CAP reform for 2023-2027. The subject of this study is to analyse the general and specific goals of the new CAP reform, as well as the adopted systemic solutions. The aim is to present the key goals, objectives and elements of the reformed CAP, particularly the most significant innovations – national strategic plans, various forms of direct payments and new environmental solutions within both pillars of CAP. The results show that strategic plans and new system solution provide a good starting point to ensure the fulfilment of the specific needs of EU farmers and rural communities, using CAP measures and instruments set in the strategic framework. The new environmental solutions have caused concern among some EU farmers and are subject to revision.